Rancang Bangun Ignition System Untuk Turbocharger Gas Turbine Engine dengan Inducer Diameter 1,75 Inch - M. Zuhal Fachri A; Wira Gauthama; Zulham Hidayat (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
Turbocharger is a centrifugal compressor that obtain power from turbines whose power source comes from vehicle exhaust gases. In this design, the turbocharger acts as the compressor and turbine functions. The goal of designing the ignition system is that the system can produce strong sparks which burn the fuel entering the combustion chamber. Thus maintaining the operational of the engine. From the calculation, it was found that the energy required to burn 0.013 kg / s LPG gas was 0.164 kW and the energy generated from the ignition system design was 326,286 kW. In conclusion, the ignition system can supply the amount of energy to burn 0.0013 kg / s LPG gas. In the turbocharger experiment, the gas turbine engine can light up and operate normally and continuously.